Enhancing organizational performance: how gender diversity enhances employee engagement and commitment - Nawal Adam; Areej Alfawaz (Humanities & Social Sciences Communications)
Abstract This study examines the multifaceted relationship between gender diversity, employee engagement, employee commitment, and organizational performance in the context of Saudi Arabia. Data from 1233 employees working in 19 organizations were collected using random sampling techniques. Using SMARTpls structural equation modeling, the study demonstrates that gender diversity significantly and positively influences employee commitment and engagement in organizations. Furthermore, the study identifies a substantial association between employee commitment, engagement, and organizational performance. The research underscores the pivotal role of gender diversity as a catalyst for enhancing organizational performance. Moreover, it highlights the essential significance of employee commitment and engagement as pivotal elements in the complex relationship between gender diversity and organizational performance. It emphasizes that organizations aspiring to achieve superior performance must prioritize cultivating and nurturing high levels of employee commitment and engagement.